0035 Gender Differences In Sleep Homeostasis: Chemogenetic Approach To Examine The Role Of Melanin Concentrating Hormone - Thakkar, Mahesh M; Sharma, Rishi; Clemmons, Dylan; Heyer, Destiny; Plessis, Jacques Du; Sharma, Abhilasha; Sahota, Pradeep (Sleep (New York, N.Y.), 2019)
Introduction Male and female have minimal differences in spontaneous sleep-wakefulness. However, gender differences have been observed in homeostatic response to sleep deprivation. Recent studies suggest that neurons containing melanin-concentrating hormone (MCH) play a crucial role in sleep regulation. More importantly, the expression of MCH and its receptors is modulated by female sex hormone, estrogen. Does MCH play a differential role in the regulation of sleep homeostasis in males and females? Methods To address this question, we used sleep deprivation (6 hours; second half of light period)-recovery sleep (3 hours) paradigm to examine sleep homeostasis and performed two experiments in C57BL/6J-cre mice (expressing cre-recombinase in MCH neurons) instrumented with sleep recording electrodes. In addition, inhibitory Designer Receptors Exclusively Activated by Designer Drug (DREADD; AAV/hSyn-DIO-hM4Di-mCherry; 300nl/site) was bilaterally infused in MCH-rich lateral hypothalamus. Experiment 1 verified if there were any gender differences between males and females in spontaneous sleep-wakefulness (S-W) and, in recovery sleep. Experiment 2 determined the effects of MCH inhibition on spontaneous S-W and recovery sleep. Chemogenetic inhibition of MCH neurons was achieved by infusion of clozapine-N-oxide (CNO, a selective DREADD receptor ligand; 5mg/kg, intraperitoneally), at light onset or during the last hour of sleep deprivation. On completion of the experiment, animals were euthanized, brains removed and processed for MCH immunofluorescence Results DREADD was expressed in >70% of MCH neurons. No gender differences were observed during spontaneous S-W. However, gender differences were observed in recovery sleep, Females during proestrus stage (high estrogen levels) spent significantly more time in recovery sleep as compared to males or females in diestrus (low estrogen levels) stage. Silencing of MCH neurons suppressed recovery sleep in both, males and females. However, the amount of recovery sleep suppressed was significantly higher in females during proestrus stage as compared to males or females during diestrus stage. Conclusion Based on the results described above, we suggest that MCH may have a causal role in increased recovery sleep observed in females during proestrus stage. Support (If Any) Department of Veterans Affairs Merit Research Award (I01BX002661)